Comparison of oral ivermectin versus crotamiton 10% cream in the treatment of scabies. (December 2014) - Goldust, Mohamad; Rezaee, Elham; Raghifar, Ramin
Abstract Objective: Scabies is a relatively contagious infection caused by a tiny mite (Sarcoptes scabiei). Products used to treat scabies are called scabicides because they kill scabies mites; some also kill mite eggs. The aim of this study was to compare the efficacy and safety of oral ivermectin versus crotamiton 10% cream for the treatment of scabies. Methods: In total, 320 patients with scabies were enrolled, and were randomized into two groups: the first group received a single dose of oral ivermectin 200 µg/kg body weight, and the second group were treated with crotamiton 10% cream and were told to apply this twice daily for five consecutive days. Treatment was evaluated at intervals of two and four weeks, and if there was treatment failure at the two-week follow-up, the treatment was repeated. Results: A single dose of ivermectin provided a cure rate of 62.5% at the two-week follow-up, which increased to 87.5% at the four-week follow-up after repeating the treatment. Treatment with crotamiton 10% cream was effective in 46.8% of patients at the two-week follow-up, which increased to 62.5% at the four-week follow-up after this treatment was repeated. Conclusion: A single dose of ivermectin was as effective as one application of crotamiton 10% cream at the two-week follow-up. After repeat treatment, ivermectin was superior to crotamiton 10% cream at the four-week follow up. The delay in clinical response with ivermectin suggests that it may not be effective against all the stages in the life cycle of the parasite.